The Effects of Multiculturalism and Diversity on Project Performance within the UAE Construction Industry - Akl, Moayyad Ahmad (2015)
Multiculturalism in workplace is the co-existence of workers or employees with diverse backgrounds, religions, and cultures. This paper aimed to investigate the effects of multiculturalism, and diversity on project performance within the U.A.E construction industry, and the challenges associated with it. Multiculturalism has a lot of pros and cons which contribute vitally the project performance. In construction industry, multiculturalism is majorly affecting the overall project performance, and by managing these cultural differences, and empowering all the individuals, this can increase their effectiveness and eliminate its effect. This paper was analyzed using the qualitative approach. Interviews were conducted to collect data from different respondents in the U.A.E. The population sample includes 20 respondents comprising of high-profile consultants, project management and contractors from UAE construction companies. It’s been noticed that most of the interviewees were aware of the importance of having a diverse workforce, and acknowledge their effect on the project performance. This study intends to explore the challenges associated with having such diverse workforce, and propose recommendations to manage, and take advantage of having multiculturalism and diversity in construction industry, which can improve the project performance massively.